Dual origin of relapses in retinoic-acid resistant acute promyelocytic leukemia - Jacqueline Lehmann-Che (Nature Portfolio, 2018)
Historical acute promyelocytic leukemia patients treated with retinoic acid and chemotherapy sometimes did relapse. Here the authors performed exome sequencing on 64 patient's samples from diagnosis/relapse/remission and show relapse associates either with cooperating oncogenes at diagnosis, or with unexpected persistence of ancestral pre-leukemic clones.